2003
DOI: 10.1097/00001888-200310000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Ethics, Professionalism, and Humanities at Michigan State University College of Human Medicine

Abstract: This article describes the variety of approaches used at Michigan State University's College of Human Medicine for teaching ethics, professionalism, and humanities to undergraduate medical students: courses in ethics and health policy; mentoring programs; selectives in history, literature, and spirituality; structured patient care experiences; and discussions with students in their clinical years on the ethical and professional challenges confronting them in their clinical experiences. Some of these approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…As noted above, curriculum and programmatic-based reform (e.g., formal course/exercises, role model training, interprofessional education initiatives) appear to be the weapons of choice to confront the HC (by enhancing humanistic attributes among institutional players [76][77][78][79][80][81][82]. Nonetheless, these reform efforts have stressed microlevel, individual-and group-oriented change.…”
Section: The Hc and Humanism-based Reform Efforts In Medical Educationmentioning
confidence: 99%
“…As noted above, curriculum and programmatic-based reform (e.g., formal course/exercises, role model training, interprofessional education initiatives) appear to be the weapons of choice to confront the HC (by enhancing humanistic attributes among institutional players [76][77][78][79][80][81][82]. Nonetheless, these reform efforts have stressed microlevel, individual-and group-oriented change.…”
Section: The Hc and Humanism-based Reform Efforts In Medical Educationmentioning
confidence: 99%
“…Michigan State University College of Human Medicine described varying components of ethics and professionalism within their curriculum that included: ethics and health policy, a mentoring program, elective offerings, and structured patient care experiences followed by discussion. 18 An innovative strategy within a professionalism course at the Warren Alpert Medical School of Brown University used structured reflective writing assignments on course topics and individualized feedback. 19 Finally, a national demonstration project with 33 medical schools found that a community-based professionalism curriculum using service-learning pedagogy was a successful approach.…”
Section: Introductionmentioning
confidence: 99%
“…Fortyeight articles described a humanities-based intervention. Twenty-six of these 48 articles did not report any formalised evaluation outcomes (Goodwin 2015, Kemp 2014, Ortega 2011, Wald 2010, Joachim 2008, Kumagai 2008, Boudreau 2007, Meites 2003, Louis-Courvoisier 2003, Frich 2003, Acuna 2003, Murray 2003, Jones 2003, Hawkins 2003, Wear 2003, Fried 2003, Spike 2003, Krackov 2003, Sirridge 2003, Andre 2003, Montgomery 2003, Kirklin 2003, Rizzolo 2002, Sklar 2002, Downie 1997, Self 1990. Of the 22 articles reporting evaluation outcomes, 12 described learner satisfaction outcomes (del Pozo 2005, Wald 2015, Gurtoo 2013, Abdel-Halim 2012, George 2011, Karnad 1999, Shapiro 2003, Newell 2003, Anderson 2003, Lypson 2002, Bertman 1985, Wilson 1980.…”
Section: Resultsmentioning
confidence: 99%
“…Several methods of integrating humanities interventions were described. A common format was small group teaching, and interventions were often facilitated by a professional with humanities experience (George 2011, Wald 2010, Gulpinar 2009, Boudreau 2007, Wachtler 2006, Karnad 1999, Shapiro 2004, Hawkins 2003, Andre 2003, Shapiro 2003, Newell 2003, Anderson 2003. Only three interventions utilized newer methods of medical education such as websites to curate content, or social media to enable more frequent communication between students (Wiecha 2002, Wiecha 2008, George 2011.…”
Section: Resultsmentioning
confidence: 99%